Resurgence and alternative‐reinforcer magnitude. Issue 2 (14th February 2017) - Craig, Andrew R.; Browning, Kaitlyn O.; Nall, Rusty W.; Marshall, Ciara M.; Shahan, Timothy A.
Abstract : Resurgence is defined as an increase in the frequency of a previously reinforced target response when an alternative source of reinforcement is suspended. Despite an extensive body of research examining factors that affect resurgence, the effects of alternative‐reinforcer magnitude have not been examined. Thus, the present experiments aimed to fill this gap in the literature. In Experiment 1, rats pressed levers for single‐pellet reinforcers during Phase 1. In Phase 2, target‐lever pressing was extinguished, and alternative‐lever pressing produced either five‐pellet, one‐pellet, or no alternative reinforcement. In Phase 3, alternative reinforcement was suspended to test for resurgence. Five‐pellet alternative reinforcement produced faster elimination and greater resurgence of target‐lever pressing than one‐pellet alternative reinforcement. In Experiment 2, effects of decreasing alternative‐reinforcer magnitude on resurgence were examined. Rats pressed levers and pulled chains for six‐pellet reinforcers during Phases 1 and 2, respectively. In Phase 3, alternative reinforcement was decreased to three pellets for one group, one pellet for a second group, and suspended altogether for a third group. Shifting from six‐pellet to one‐pellet alternative reinforcement produced as much resurgence as suspending alternative reinforcement altogether, while shifting from six pellets to three pellets did not produce resurgence. These results suggest that alternative‐reinforcer magnitude has effects on elimination and resurgence of target behavior that are similar to those of alternative‐reinforcer rate. Thus, both suppression of target behavior during alternative reinforcement and resurgence when conditions of alternative reinforcement are altered may be related to variables that affect the value of the alternative‐reinforcement source.